Hubungan Dukungan Keluarga, Dukungan Perawat, Resiliensi Dengan Kecemasan Pasien Penyakit Ginjal Kronis Dengan Hemodialisis Akibat Pandemik Covid-19 - Ni Luh Widani (Universitas Malahayati Lampung, 2022)
ABSTRACT The risk of infection with COVID-19 is higher for someone with comorbidities. Kidney failure patients on hemodialysis (HD) have several comorbidities such as diabetes, kidney failure, heart disease, and lung disease. Patients are very vulnerable to experiencing anxiety and patients need family support, nurse support, and resilience in the face of the COVID-19 pandemic. Quantitative research with descriptive correlative design with a cross-sectional method. This study was conducted on 93 patients who routinely undergo HD therapy from September - to October 2020. Quantitative research with descriptive correlative design with the cross-sectional method. This study was conducted on 93 patients who routinely undergo HD therapy from September - October 2020. Univariate analysis is the majority of respondents aged 41-60 years (43%), male (54.8%), Higher education (54.8%), duration of HD 24-60 months (50 %), good family support (65.6%), good nurse support (55.9%), moderate resilience 62.4% and 60.2% not anxious. The results of the Kendal tau-C test analysis showed that there was a statistically significant relationship between the level of resilience (p-value=0.025; p0.05) and anxiety. There was no significant relationship between family support (p-value 0.290) and no relationship between care support (p-value 0.151); (p0.05) with anxiety. The level of resilience of CKD patients with HD is related to patient anxiety in this Covid-19 pandemic. Keywords: Family Support, Health Worker Support, Hemodialysis, Resilience ABSTRAK Risiko infeksi COVID-19 lebih berisiko pada seseorang dengan komorbid. Pasien gagal ginjal dengan hemodialisis (HD) memiliki beberapa komorbiditas seperti diabetes, gagal ginjal, penyakit jantung, dan penyakit paru-paru. Pasien sangat rentan mengalami kecemasan dan pasien membutuhkan dukungan keluarga, dukungan perawat, dan resiliensi dalam menghadapi pandemic covid-19. Tujuan mengedentifikasi kecemasan pasien, menganalisis hubungan antara dukungan keluarga, dukungan perawat, resiliensi dengan kecemasan pasien penyakit ginjal kronis dengan hemodialisis dalam pandemic COVID-19. Jenis penelitian kuantitatif desain deskriptif korelatif, cross-sectional. Responden pasien rutin menjalani terapi HD di RS X Jakarta Pusat sebanyak 93 orang pada Bulan September – Oktober 2020 yang memenuhi kriteria. Analisa univariate mayoritas responden dengan dukungan keluarga baik (65,6%), dukungan perawat baik (55,9%), tingkat resiliensi sedang 62,4% dan tidak cemas 60,2%. Hasil analisis uji Kendal tau-C didapatkan secara statistik ada hubungan yang bermakna antara tingkat resiliensi (p-value=0,025 ;p0,05) dengan kecemasan. Tidak ada hubungan bermakna dukungan keluarga (p-value 0,290) dan hubungan dukungan perawatan (p-value 0,151) ; (p0,05) dengan kecemasan. Tingkat resiliensi pasien PGK dengan HD ada hubungan dengan kecemasan pasien dalam pandemic Covid-19 ini. Kata Kunci: Dukungan Keluarga, Dukungan Petugas Kesehatan, Hemodialis, Resiliensi